2018
DOI: 10.1136/bmjdrc-2018-000515
|View full text |Cite
|
Sign up to set email alerts
|

Intent-to-treat analysis of a simultaneous multisite telehealth diabetes prevention program

Abstract: ObjectiveDetermine the effectiveness of a 16-week modified diabetes prevention program (DPP) administered simultaneously to multiple rural communities from a single urban site, as compared with a similar face-to-face intervention. A 12-week intervention was evaluated to consider minimization of staff costs in communities where resources are limited.Research design and methodsA prospective cohort study compared DPP interventions implemented in rural (via telehealth technology) and urban (face-to-face) communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…In the ENHANCED randomized controlled trial, a dietician nutritionist‐led telemedicine program resulted in improvement in diabetes care measures (haemoglobin A1c <8%, blood pressure <140/90 mmHg, tobacco cessation, statin use, and aspirin use appropriate) compared to the control arm 63 . Importantly, studies have shown that telemedicine delivery of a T2DM prevention program was non‐inferior to an in‐person program, suggesting that telemedicine could become an important mechanism to deliver care in areas with reduced access to providers 64,66 . These results require replication in other cohorts, but are reassuring for providers and facilities implementing telemedicine based care for rural patients.…”
Section: Resultsmentioning
confidence: 91%
“…In the ENHANCED randomized controlled trial, a dietician nutritionist‐led telemedicine program resulted in improvement in diabetes care measures (haemoglobin A1c <8%, blood pressure <140/90 mmHg, tobacco cessation, statin use, and aspirin use appropriate) compared to the control arm 63 . Importantly, studies have shown that telemedicine delivery of a T2DM prevention program was non‐inferior to an in‐person program, suggesting that telemedicine could become an important mechanism to deliver care in areas with reduced access to providers 64,66 . These results require replication in other cohorts, but are reassuring for providers and facilities implementing telemedicine based care for rural patients.…”
Section: Resultsmentioning
confidence: 91%
“…If smokers did not attend the follow-up, their ACSD at the most recent follow-up was used as the outcome of the current follow-up, as was their smoking cessation status. Related studies have shown that using ITT followed by analysis leads to conservative results ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…Of the 83 programs, 16 (19%) were either delivered to groups of participants or included a component that involved groups of participants. Of these 16 programs, 5 (31%) targeted diabetes education, self-management, and behavior change coaching [101,102,108,116,125]; 4 (25%) programs were CVD rehabilitation (secondary prevention) or counseling programs [46,47,52,53,55,57]; 4 (25%) addressed risk factors for chronic disease through education and behavior change coaching [131,132,136,141]; 1 (6%) involved group cognitive behavioral therapy (CBT) for participants experiencing insomnia [66]; 1 (6%) involved pharmacist-led group education for hepatitis C [73]; and 1 (6%) involved group education for osteoarthritis [70].…”
Section: Program Design: Group Programs Co-design and Guiding Theoriesmentioning
confidence: 99%